DIFFICULTIES IN THE DIAGNOSIS AND SURGICAL TREATMENT OF XANTOGRANULOMATOUS PYELONEPHRITIS - E. Enchev; G. Minkov; E. Dimitrov; S. Nikolov; A. Petrov; Iv. Ovcharov; Y. Yovtchev (Trakia Journal of Sciences)
Purpose: The diagnosis of xanthogranulomatous pyelonephritis is primarily histological. The mandatory studies that have to be performed are: abdominal echography, excretory urography, CT, and renal angiography. Methods: The current report covers a period of 16 years (1992-2008) and presents clinical material from 9 patients with a long history of nephrolithiasis. In the past, six of them have undergone surgical or extracorporeal lithotripsy. Results and conclusion: The performed preoperative imaging studies showed kidney tumors, and the operative treatment method used was nephrectomy. The post-operative follow-up did not detect any complications in any of these patients.